Development and Feasibility Validation of Science-Edutainment Digital Videos for Foundational Geography Concepts - Rani Kurnia; Azni Fajrilia; Diah Wijayanti; Chalia Chistella; Aliya Amani Sharul Nizar (CV Bumi Spasial, 2026)
Foundational geography curriculum is often perceived as a cognitive Foundational geography concepts often present cognitive challenges for secondary school students because they require learners to connect abstract definitions, spatial principles, material objects, and geographical approaches with observable real-world phenomena. This study aimed to develop and validate science-edutainment digital videos designed to support students' visualization of foundational geography concepts. A Research and Development design was employed using a modified 4D model limited to the Define, Design, and Develop stages. The Define stage involved curriculum analysis, media analysis, and student characteristics analysis at SMAN 1 Bululawang. The Design stage produced scripts, storyboards, validation instruments, and video prototypes. The Develop stage involved expert validation and user feasibility testing with one media expert, one subject-matter expert, four geography teachers, and 32 Grade XI social science students. Data were collected through validation sheets and feasibility questionnaires and analyzed using descriptive percentages. The results showed that media expert validation reached 99%, subject-matter expert validation reached 95%, teacher responses reached 89%, and student responses reached 88%, all categorized as very feasible. These findings indicate that science-edutainment digital videos are feasible as supplementary media for foundational geography learning. However, further studies are needed to examine the effectiveness of the developed videos in improving students' conceptual understanding, spatial thinking, and geospatial literacy.